WAKE UP ONLINE WEBSITE DESIGN POLL - Edy Ruslan; Eko Hardiyanto. SSi. MMSi (Jurnal Sistem Informasi, 2001)
This website application online poll will be very useful for collecting activity data.By using this website online poll, can overcome the constraints faced in the pollsduring this manual.Website this poll is very easy to use by the system administrator or the provider of thewebsite because it has administrative functions via the admin panel in charge ofchanging and adding a poll question.